2015
DOI: 10.17818/nm/2015/si3
|View full text |Cite
|
Sign up to set email alerts
|

A Proposal for the Optimization of Storage Areas in a Selected Enterprise

Abstract: The current tough competition prevalent within the market economy is forcing business entities to achieve efficiency in their processes. This also applies to the transfer of goods from point A to point B, which is the subject of transportation. This process is influenced by many factors. It is necessary to not only consider the time,i.e. the fact that the required goods must be delivered in time, but it is also essential to take the financial aspect linked into account, for example, with the cost items such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In turbulent changing business environment only those companies that understand the current trends in global economy may survive Mura and Gašpariková, 2010;Li and Jiang, 2016). To be able to react to this situation as well as to ensure the sustainability and continuous development and due to the tough competition, managers strive to build in their enterprises a functioning process because business entities have to achieve efficiency in their processes (Čambál and Caganova, 2010;Urbancová and Fejfarová, 2017;Němec et al, 2015). Companies must invest great effort in development of management system that will ensure their survival on the market (Klarić et al, 2015;Plchová and Turáková, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In turbulent changing business environment only those companies that understand the current trends in global economy may survive Mura and Gašpariková, 2010;Li and Jiang, 2016). To be able to react to this situation as well as to ensure the sustainability and continuous development and due to the tough competition, managers strive to build in their enterprises a functioning process because business entities have to achieve efficiency in their processes (Čambál and Caganova, 2010;Urbancová and Fejfarová, 2017;Němec et al, 2015). Companies must invest great effort in development of management system that will ensure their survival on the market (Klarić et al, 2015;Plchová and Turáková, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the differences between men and women in working values can be reflected in differences in motivational factors. Several studies (Lepold et al, 2018;Sánchez-Sellero et al, 2018, Kertész et al, 2017Němec et al, 2015;Sanchez-Sellero et al, 2013;Kropivšek et al, 2010;Osabiya, 2015) have shown that men earn more than women. One possible explanation is that male values of work lead to greater productivity in a traditional work environment and the reason for higher wages may be their greater labour value.…”
Section: Resultsmentioning
confidence: 99%
“…Last but not least, the financial equivalent for the replacement of the upper roadway layer or the whole roadway construction is based on approved cost databases, but it can´t be generalized to all roads of the same class (each road administrator of the given road uses apart from these cost databases its own pricelists). In spite of all these deficiencies, the analytical model also brings into the calculation of total costs I 2 other factors in accordance with [5,[18][19][20][21], which have a major effect on the negative impacts of the diverted traffic flow. These externalities are subsequently expressed by the financial equivalent, of which is the road administrator in case of higher intensities (proportion) of heavy freight vehicles more loaded compared to the road management in normal operation.…”
Section: Discussionmentioning
confidence: 99%